Jawabanmu

2014-09-04T17:42:03+07:00
2√25.7  -  5√49.7 +  √9.7 - 3√16.7    --------------->  b√a².c = ab√c, karena √a²=a
2√5².7   -  5√7².7  + √3².7 - 3√4².7
2.5√7    -  5.7√7    + 3√7  - 3.4√7
10√7  - 35√7 + 3√7  - 12√7  --------------> a√b - c√b + d√b = a-c+d√b
(10-35+3-12)√7 = -34√7
1 1 1
2014-09-04T17:47:13+07:00
2 √175 - 5 √343 + √63 - 3 √112 = 2 √25. 7 - 5 √49. 7 + √9. 7 - 3 √16. 7
                                                  = 2 √25 √7 - 5 √49 √7 + 3 √7 - 3 √16 √7
                                                  = 2. 5 √7 - 5. 7 √7 + 3 √7 -3. 4 √7
                                                  = 10√7 - 35√7 + 3√7 - 12√7
                                                  = (10 - 35 + 3 -12) √7                         (difaktorkan)
                                                  = -34 √7
1 5 1